2018
DOI: 10.1007/s00253-018-9353-2
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering bacterial xylose metabolism and metabolic engineering of industrial microorganisms for use as efficient microbial cell factories

Abstract: The goal of sustainable production of biochemicals and biofuels has driven the engineering of microbial cell as factories that convert low-value substrates to high-value products. Xylose is the second most abundant sugar substrate in lignocellulosic hydrolysates. We analyzed the mechanisms of xylose metabolism using genome sequencing data of 492 industrially relevant bacterial species in the mini-review. The analysis revealed the xylose isomerase and Weimberg pathways as the major routes across diverse routes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 63 publications
0
16
0
1
Order By: Relevance
“…Since xylose reductase and xylitol dehydrogenase are usually cofactor dependent, overexpression of these genes will result in the imbalance of cofactors in Z. mobilis and lead to the accumulation of the deleterious intermediate xylitol [ 31 ]. Therefore, in the present study, we evaluated the effect of overexpression of xylose isomerase (XI) and xylulokinase in xylose-utilization recombinant strain Z. mobilis 8b to avoid this problem, which can convert xylose to xylulose-5-phosphate without cofactors.…”
Section: Introductionmentioning
confidence: 99%
“…Since xylose reductase and xylitol dehydrogenase are usually cofactor dependent, overexpression of these genes will result in the imbalance of cofactors in Z. mobilis and lead to the accumulation of the deleterious intermediate xylitol [ 31 ]. Therefore, in the present study, we evaluated the effect of overexpression of xylose isomerase (XI) and xylulokinase in xylose-utilization recombinant strain Z. mobilis 8b to avoid this problem, which can convert xylose to xylulose-5-phosphate without cofactors.…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary synthetic biology and metabolic engineering offer the possibility of expanding the substrate range of microbial cell factories beyond the sugars typically used as carbon sources (Calero and Nikel, ; Prather, ). Examples of this sort of metabolic manipulation for broadening substrate ‘palatability’ of bacteria include several chemical species, ranging from simple C1 compounds such as CO 2 or HCOOH (Antonovsky et al., ; Yishai et al., ) to structurally complex substrates such as lignocellulosic materials derived from biomass (Beckham et al., ; Barton et al., ; Kim and Woo, ). Alcohols conform a special category of alternative substrates for biotechnology, and they are currently being discussed as promising renewables for sustainable bioproduction (Stowell et al., ; Smith, ; Dahod et al., ; Hoffmann et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…A genome analysis of 492 bacteria strains of Bacillus, Bifidobacterium, Caulobacter, Corynebacterium, Escherichia, Lactobacillus, and Xanthomonas and the search for genes involved in xylose metabolism have been performed. The analysis revealed that the pathways of XI and Weimberg were the prevalent routes, with the XI pathway being the best preserved (Figure 1) [100].…”
Section: Xylose Metabolic Network In Bacteriamentioning
confidence: 99%